تأثير معالجة المهام المزدوجة (Dual – Task) على تحسين زمن رد الفعل البسيط بمهارة 100م عدو لدى طلاب كلية التربية الرياضية - فاضل, رغد; ماضي, انجيلا; نيوف, غيداء (Latakia University Journal -Medical Sciences Series, 2017)
هدفت الدراسة الحالية إلى تحسين زمن رد الفعل في سباق 100م عدو من خلال التركيز على معالجة المعلومات داخل الجهاز العصبي المركزي ومعرفة فيما إذا كان للتجربة المطبقة مخبرياً أثر على التدريب الميداني. ولهذا الغرض تم تصميم برنامج تدريب مخبري بالاعتماد على دراسات تجريبية مخبرية هدفت إلى معرفة كيفية معالجة المعلومات في الدماغ والمرحلة الأكثر تأثراً عند معالجة منبهين متزامنين (Dual-Task) بواسطة برنامج لقياس زمن رد الفعل في المخبر. تكونت عينة البحث من 32 طالباً من طلاب كلية التربية الرياضية وتم استخدام المنهج التجريبي بأسلوب المجموعتين المتكافئتين ( تجريبية – ضابطة ). خضعت المجموعة التجريبية بالإضافة إلى محاضراتهم العملية إلى برنامج مخبري طلب فيه معالجة منبهين في نفس الوقت (سمعي – تذكر أحرف ). وقد قيس زمن رد الفعل على المنبه السمعي ميدانياً قبل تطبيق التجربة المخبرية وبعدها كما تمت مقارنته مع زمن رد الفعل للمجموعة الضابطة.توصلت الدراسة إلى تحسن زمن رد الفعل على صوت المنبه لدى المجموعة التجريبية وعليه هناك تأثير إيجابي للبرنامج المطبق مخبرياً على النتائج الميدانية. ومن هنا أوصينا بضرورة التنويع في الأساليب التدريبية ومنها التي تركز على المعالجة العقلية للحصول على نتائج أداء أفضل. The current research aimed at improving the reaction time in the 100-meter running race through focusing on information processing inside the central nervous system. It also aimed at discovering if the experiment performed in the laboratory had an effect on the field training. For this purpose, an experimental training program based on laboratory empirical studies was designed to find out how the information was processed in the brain and to define the most influenced phase when two concurrent stimuli were being processed by software for reaction time in laboratory. The sample research consisted of 32 students from the Faculty of Physical Education. The empirical approach was used based on the two equivalent groups method (experimental – control). The experimental group, besides their practical lectures, were subjected to an experimental program where they were asked to process two stimuli simultaneously (auditory – letter recall). The reaction time to the auditory stimulus was measured in field before and after the laboratory experiment was applied and it was compared with the reaction time of the control group.The research proved to Improve the reaction time to the Sound of the stimuliauditory of the experimental group and the positive Impact it there for the program applied to laboratory and field results . So, we recommended the need and necessity of diversification in training methods such as mental processing in order to achieve results of better performance.